2022
DOI: 10.3390/antibiotics11030376
|View full text |Cite
|
Sign up to set email alerts
|

Does the COVID Pandemic Modify the Antibiotic Resistance of Uropathogens in Female Patients? A New Storm?

Abstract: Urinary tract infections (UTIs) represent a common pathology among female patients, leading to overprescribing antibiotics, globally. The emergence of the COVID-19 pandemic has dramatically increased the incidence of this particular viral pneumonia with secondary bacterial superinfection, resulting in continuous therapeutic or prophylactic recommendations of antibiotic treatment; thus, an updated analysis of current antimicrobial resistance among uropathogens is mandatory. This cross-sectional retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 51 publications
3
20
1
Order By: Relevance
“…6% in our group, ranging from 5.54% to 8.4% in other studies and Pseudomonas spp. 6% in our group, ranging from 2.59% to 7.28% in other studies [ 11 , 37 , 38 ],…”
Section: Discussionsupporting
confidence: 52%
“…6% in our group, ranging from 5.54% to 8.4% in other studies and Pseudomonas spp. 6% in our group, ranging from 2.59% to 7.28% in other studies [ 11 , 37 , 38 ],…”
Section: Discussionsupporting
confidence: 52%
“…From 2020 to 2022, it has been reported that the bacterial spectrum and AMR have changed during the COVID-19 pandemic [44][45][46] . During the COVID-19 pandemic, China had many policies, including restrictions on social interaction, wearing masks, isolation, and quarantine, to reduce the spread of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of multidrug resistance (MDR) in bacteria has become one of the most daunting challenges of the 21st century, due to the increasing prevalence of difficult-to-treat infections and the lack of relevant therapeutic alternatives [14][15][16]. The magnitude of the issue has also been identified by political leaders, exemplified by the recent commitment of the G7 Nations to resistance surveillance and to invest in antimicrobial research [17].…”
Section: Introductionmentioning
confidence: 99%